Zeta Potential Mechanisms Applied to Cellular Immobilization: A Study with Saccharomyces cerevisiae on Dye Adsorption - Mendes, Carolina Rosai; Dilarri, Guilherme; Stradioto, Marcia Regina; Lopes, Paulo Renato Matos; Bidoia, Ederio Dino; Montagnolli, Renato Nallin (Journal of polymers and the environment, 2021)
The wastewater discharge from the textile industry is a major threat to environmental safety, especially for developing countries. In this context, we proposed a biopolymer-based strategy to mitigate this issue. A new kind of immobilization by the zeta potential from Saccharomyces cerevisiae cell in the chitosan was tested. Two novel materials were produced and characterized: Chitosan beads (CB) synthesized by the ionotropic gelation technique, and chitosan beads with immobilized S . cerevisiae by zeta potential (CBY), both targeting the Acid Blue 25 dye removal from aqueous solutions. FT-IR and MEV analyses were used to investigated and monitoring the mechanism of cellular interaction with the biopolymer. We observed that the cell wall of yeasts had a negative zeta potential, confirming electrostatic interactions between the cell and the biopolymer that improved their immobilization. Kinetics, adsorption isotherms, thermodynamics, and matter behaviour supported our evidences. Kinetic studies showed that CBY reached kinetic equilibrium in 240 min and qe (exp) = 28.201 μg mg −1 . The CB reached equilibrium at 330 min and qe (exp) = 17.518 μg mg −1 . Therefore, the materials allowed intraparticle diffusion towards the mesopore layers. Thermodynamics showed that adsorption was spontaneous and influenced by temperature. Both CB and CBY underwent swelling during adsorption due to their own hydrophilicity, leading up to 204% increase in volume compared to dry beads. These experiments were supplemented by ecotoxicity assays evaluating Daphnia similis interactions with Acid Blue 25 dye solutions before and after the adsorptive treatment. Bioassays showed a significant decrease in toxicity after the adsorption using CBY.